New insights into retroviral Gag–Gag and Gag–membrane interactions - Maldonado, José O.; Martin, Jessica L.; Mueller, Joachim D.; Zhang, Wei; Mansky, Louis M. (Frontiers in Microbiology, 2014)
A critical aspect of viral replication is the assembly of virus particles, which are subsequently released as progeny virus. While a great deal of attention has been focused on better understanding this phase of the viral life cycle, many aspects of the molecular details remain poorly understood. This is certainly true for retroviruses, including that of the human immunodeficiency virus type 1 (HIV-1) as well as for human T-cell leukemia virus type 1 (HTLV-1). This review discusses the retroviral Gag protein and its interactions with itself, the plasma membrane and the role of lipids in targeting Gag to virus assembly sites Recent progress using sophisticated biophysical approaches to investigate – in a comparative manner – retroviral Gag-Gag and Gagmembrane interactions are discussed. Differences among retroviruses in Gag-Gag and Gag-membrane interactions imply dissimilar molecular aspects of the viral assembly pathway, including the interactions of Gag with lipids at the membrane.